The debate as one of the avenues of political preparation of students ISP - Lidia Cira Carbonell Izquierdo; Juan Alberto Blanco Rivera (Revista MENDIVE, 2003)
This article refers to work with Political Debates and submit to the consideration of all stakeholders, modest reflections on a subject that, in our view, should be revitalized from taking as reference its own conception. The goal is to make them aware of the proper use of one of the resources needed for it: the question that stimulates a logical and reflective thinking and the variety of responses. It is the intention of the authors also establish a dialogue with readers to know what is happening in pedagogical practice.